2019
DOI: 10.15314/tsed.522984
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Leisure Benefits on Leisure Satisfaction: Extreme Sports

Abstract: In this study, it was aimed to investigate the effect of leisure benefit on leisure satisfaction in extreme sports athletes. In order to determine the leisure satisfaction level of participants, Leisure Satisfaction Scale developed by Beard and Ragheb (1980) and adapted to Turkish by Gökçe and Orhan (2011) was used. Leisure benefit scale developed by Ho (2008) and adapted into Turkish by Akgül, Ertüzün, and Karaküçük (2018) was used to measure the perceived benefit from recreational activities. The conventiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 13 publications
(14 reference statements)
0
15
0
2
Order By: Relevance
“…Those findings suggest that screen golf has high accessibility for everyone and that it is a quality alternative to participating in traditional golf for the increasing golfer population. It has previously been found that leisure satisfaction predicted psychological wellbeing and sports activities have a positive effect on the participant's psychological well-being [25][26] [27].…”
Section: Discussionmentioning
confidence: 99%
“…Those findings suggest that screen golf has high accessibility for everyone and that it is a quality alternative to participating in traditional golf for the increasing golfer population. It has previously been found that leisure satisfaction predicted psychological wellbeing and sports activities have a positive effect on the participant's psychological well-being [25][26] [27].…”
Section: Discussionmentioning
confidence: 99%
“…We need to make use of the time well, have activities that we like to do, and continue to interact with other people within the limitations and obstacles (Stieg, 2020). It is known that individuals participating in recreational activities are happy and healthy (Eskiler, Yıldız & Ayhan, 2019). Having knowledge about and applying recreational events and activities aimed at eliminating the negative effects of permanent homestay will prevent mental and physical regression and provide morale and motivation within the family while developing personal skills (Yildiz, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…A group activity helps the individual fulfill their desire to socialize, to belong to a group (Hills & Argyle, 1998;Csikszentmihalyi & Hunter, 2003;Kim, Scott & Oh, 2005;Parfitt & Eston, 2005;Kikuga et. al, 2017;Eskiler, Yıldız & Ayhan, 2019). For example, an individual who complains of loneliness finds the opportunity to be at the same level with the same status by moving away from the characteristics of the society such as language, religion, economic status, position, race, nationality and education.…”
Section: Benefits Of Recreationmentioning
confidence: 99%